Etnomatematika pada Tradisi Tarian Negu Korung di Daerah Sumba Tengah dalam Konsep Pembelajaran Matematika - Yuniarto, Eko; Damayanti, Nia Wahyu; Boyi, Monika Ana (Jurnal Likhitaprajna, 2022)
This study aims to determine ethnomathematical learning in the people of Central Sumba which can be understood in its cultural elements. This research is a type of qualitative research that uses descriptive research methods. The subjects in this research are individuals who are experts in their fields. This research was conducted in February in Central Sumba district. The result of this research is that there are mathematical concepts that exist in several cultures in Central Sumba such as the shape of the traditional Negu Korung and Gadung dances which are circular, then the Kaddi cloth is rectangular and the calculation of the harvest results has a relationship with multiplication. With this research, it is clear that culture can be the most effective way of understanding mathematical concepts.